VISUALISASI BUDAYA LOKAL KARAPAN SAPI PADA PROGRAM ACARA NEGERI INDONESIA EPISODE SAPI MADURA - Priaska, Zharfian Raditya; Atmaja, Nur Rahmat Ardi Candra Dwi (Seni Media Rekam ISI Surakarta, 2017)
The visualization of local culture of cow karapan in Madura Cattle episode is found in the analysis of shooting technique which includes image size,shooting angle,and camera movement. The type of research used is descriptive qualitative. Data obtained through observation and literature study. Data analysis techniques consist of several stages that take place interactively,namely: data reduction, data presentation, and withdrawal of conclusions and verification.The results of this study indicate the dominance of taking a medium shot image size that gives the impression closer to the activity of individuals and groups between humans and animals related to the local culture of karapan sapi.While the dominance of the use of eye level image shooting angle has the impression of similarity in the sense that cows are treated just like humans.The use of panning camera movement dominance gives the impression of following the activity of the object.Keywords:Visualization,TVRI Jawa Timur, camera technique, Karapan Sapi.